2014
DOI: 10.1002/cbic.201402045
|View full text |Cite
|
Sign up to set email alerts
|

Protein Arginine N‐Methyltransferase Substrate Preferences for Different Nη‐Substituted Arginyl Peptides

Abstract: Protein arginine N-methyltransferases (PRMTs) catalyze methyl-group transfer from S-adenosyl-L-methionine onto arginine residues in proteins. In this study, modifications were introduced at the guanidine moiety of a peptidyl arginine residue to investigate how changes to the PRMT substrate can modulate enzyme activity. We found that peptides bearing Nη-hydroxy or Nη-amino substituted arginine showed higher apparent kcat values than for the monomethylated substrate when using PRMT1, whereas this catalytic prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The structures in Fig. 2c, and d are supported by our current and previous work (Lakowski and Frankel 2009;Lakowski et al 2010a;Lakowski et al 2013;Thomas et al 2014) and by other studies (Shek et al 2006). The structures of dimethylated primary product ions derived from aDMA and sDMA and having 158.1 m/z are proposed based on primary product ion spectra of arginine that showed a 130.0 m/z product ion with a similar structure but no methyl groups (Shek et al 2006).…”
Section: Resultssupporting
confidence: 85%
“…The structures in Fig. 2c, and d are supported by our current and previous work (Lakowski and Frankel 2009;Lakowski et al 2010a;Lakowski et al 2013;Thomas et al 2014) and by other studies (Shek et al 2006). The structures of dimethylated primary product ions derived from aDMA and sDMA and having 158.1 m/z are proposed based on primary product ion spectra of arginine that showed a 130.0 m/z product ion with a similar structure but no methyl groups (Shek et al 2006).…”
Section: Resultssupporting
confidence: 85%
“…The purpose of the current research was to use steady‐state enzyme kinetics to further explore PRMT1's methylation activity, in terms of catalytic mechanism and degree of processivity, with several biologically relevant peptide substrates. Our lab previously studied the effect of univalent isosteric replacement of the methyl group in MMA with a hydroxy substituent, which lowered the p K a of the arginine guanidino group from 12.5 to 8.7, and found that it was amenable to methylation . Here, we demonstrate that hydroxy‐substituted substrates behave similarly to monomethylated substrates and, in the context of the H4 peptide, result in the strongest substrate inhibition.…”
Section: Introductionmentioning
confidence: 68%
“…Unmethylated, monomethylated, and hydroxylated versions of peptides representing the following PRMT1 substrates were studied: histone H4 (H4), eukaryotic initiation factor (eIF4A1), and two fibrillarin‐based peptides (KRK and RKK) . An acetylated version of the fibrillarin‐based (R1) peptide from our previous study on arginine isosteres was used as a reference substrate for comparison with other peptide sequences (Table ). The hydroxylated peptides were used to investigate the differences in PRMT1 kinetics between monomethylated and hydroxylated isosteric substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) was obtained that showed inhibition against PRMT1 (13.9 μM), PRMT4 (35.7 μM) and PRMT6 (29.0 μM) [82]. A similar effect was observed for N η -nitro-substituted arginine 25 (IC 50 26-47 μM for PRMT1, 4 and 6) when studying the effects of substitution on the methylation kinetics of PRMTs[84]. Small modifications of the side chain of an arginine residue in an HIV Tat peptide sequence resulted in micromolar K i values against PRMT1 (2.7-7.6 μM) and PRMT6 (19.9-100 μM) with no significant inhibition of PRMT4[83].…”
mentioning
confidence: 66%